SISTEM INFORMASI PENGELOLAAN DATA INVENTORY MENGGUNAKAN ALGORITMA SEQUENTIAL SEARCH PADA BENGKEL MOBIL BPM AUTOWORK - Lubis, Hendarman; Ramadhan, Muhammad Fachri (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2024)
Sequential Search is a simple search algorithm that searches for elements in a list one by one until the element you're looking for has been found or until all elements have been checked. This algorithm can search for elements in arrays or lists and is usually used for smaller lists. BPM Autowork is a car repair shop that provides maintenance services on cars, and buying and selling components on cars. In the process of collecting inventory, BPM Autowork has not been maximally compurterized and tends to use manual methods for overall data collection such as using general ledgers. That way BPM Autowork is still constrained in finding data on buying and selling car components, so it takes a lot of time to find data. Thus, the Sequential Search method was created to minimize the amount of time wasted in searching for a lot of data and become more effective, practical and efficient.